PENGGUNAAN METODE INQUIRY UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA SD N 2 HARAPAN JAYA - Febri Harlina (STKIP Al Islam Tunas Bangsa dan HEPI Korda Lampung, 2021)
The purpose of this research is to increase the activities and learning outcomes of science learning the properties of objects using the Inquiry method for the fourth grade students of Elementary School 2 Harapan Jaya Bandar Lampung in 2019. The research method used was Classroom Action Research (PTK). Each cycle is carried out for 3 x (2 x 35) minutes which consists of 4 stages, namely planning, observing, and reflecting. The results of the research in each cycle in science learning the properties of objects in class IV students in 2019 are as follows: (1) in cycle I the learning activities of students in the good category only reached 61%, in cycle 2 it reached 72% and in cycle 3 it reached 80 % of students learning activities follow science learning. The conclusion of this study is that the Inquiry method can improve the activity and learning outcomes of Natural Science learning the properties of objects in grade IV elementary school 2 Harapan Jaya Kec. Tanjung Karang Barat Bandar Lampung in 2019.